US-Like Strain of Porcine Epidemic Diarrhea Virus Outbreaks in Taiwan, 2013–2014 - LIN, Chao-Nan; CHUNG, Wen-Bin; CHANG, Shu-Wei; WEN, Chi-Chi; LIU, Hung; CHIEN, Chi-Hsien; CHIOU, Ming-Tang (Journal of Veterinary Medical Science, 2014)
Since late 2013, several outbreaks of porcine epidemic diarrhea virus (PEDV) infection have emerged in Taiwan. Suckling piglets under 2 weeks of age showed severe vomiting and watery yellowish diarrhea with morbidity and mortality ranging from 80 to 100% and 90 to 100%, respectively. A total of 68 samples from 25 pig farms were confirmed as positive for PEDV and negative for rotavirus and transmissible gastroenteritis virus by reverse transcription PCR, and the partial S gene of PEDV was analyzed. Phylogenetic analysis places all 18 Taiwanese PEDV isolates collected during this outbreak in the same clade as the US strains of PEDV. This novel PEDV is prevailing and currently causing severe outbreaks in Taiwan.